Zoned out: land use policy and the unhoused in Des Moines, Iowa - Stock, Bethany Danielle (My University, 2025)
According to a recent HUD report, at least 582,500 Urban Americans are unhoused on any night. The US Midwest, known for cheap land, affordability, and relaxed pace of life, is seeing an influx of people moving to escape the high costs of living on the coasts. However, the Midwest faces a housing affordability crisis like the rest of the US. The housing market controlled by land use regulation and policy plays a key role in the unhoused, often overshadowed by significant factors like addiction or health, typically emphasized in policy discussions. As housing costs rise, more people face instability, creating a greater risk of becoming unhoused — increasing the severity of risk in cities with lower average rents, where residents have fewer affordable housing. With this focus, this research asks how land-use policy and decision-making contribute to unhoused urban residents’ displacement and continued lack of housing. It aims to expose how current land-use policies and strategies have contributed to the displacement of the most vulnerable residents and their support services in Des Moines. Des Moines outsources all service provision for the unhoused, creating a disconnect from the situation. Using a case study approach rooted in semi-structured interviews with private, public, and non-profit stakeholders, we aim to learn where the location of services for the unhoused reside, how the areas are affected by zoning, what influences decisions on development location, and how these planning decisions lead to displacement through land use policy. Both residents and developers in Des Moines face significant obstacles, including market constraints, regulatory policies, and restrictive zoning codes, which disproportionately impact low-income residents by limiting affordability, housing choice, quality, assistance, and maintenance. At the same time, developers struggle with restrictive funding requirements, zoning limitations, form-based code costs, and the need for a high return on investment, all of which contribute to a lack of diverse housing options and increased housing instability for vulnerable populations.
Keywords: Policy; Des Moines; Planning; Homelessness; Form-based code; Housing